Perception of Students Regarding Gender based Violence. - Muzaffar A1, Shenoy VK2, Vaswani VR3, Badiadika KK4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The study is undertaken to explore perception of students regarding violence against women with specific reference to domestic violence and sexual violence.Methods: This is a descriptive cross-sectional questionnaire based exploratory study conducted in Mangalore, Karnataka, India. 220 participants consisting of age group between 18 to 25 years were included. Responses were obtained from the study participants through open and close ended questionnaires. Results: More than half (60%) of medical students and (56%) of engineering students disagree that in modern India women are enjoying equal rights to men. Three forth (77% male, 82% female) of students believe and disagree that it is alright for a man to beat his wife in order to make her obedient. Two forth (61%) of medical students and (63%) of engineering students agree that throwing acid on a woman to cause disfiguration is an example of gender based violence. Conclusion: The perception of medical and engineering students regarding gender based violence is quite similar. This study brought out issues of increased violence against women. A significant number still felt that dressing of a woman may be a factor for sexual assault. Women are still facing gender inequality and are not getting equal rights to men. Even though incidence of harassment, domestic violence are on the rise, women are not ready to report about their suffering because of social and family pressure. There is also need for awareness to be bought in gender mainstreaming for educating all sectors of the society.